Green Synthesis and Structural Properties of Titanium Dioxide Nanoparticles - Bassima M. Mashkour (Academia Open, 2025)
General Background: Titanium dioxide (TiO₂) nanoparticles are widely utilized in photocatalysis, solar cells, and environmental remediation due to their chemical stability and unique polymorphic properties. Specific Background: Traditional synthetic methods often rely on hazardous chemicals, motivating interest in green synthesis using plant-based reducing agents. Knowledge Gap: Despite the promise of eco-friendly approaches, there remains a need for efficient, scalable methods that ensure high crystallinity, controlled morphology, and minimal organic residues. Aims: This study aimed to develop a sustainable synthesis of TiO₂ nanoparticles using potato peel extract as a natural reducing and stabilizing agent, replacing toxic reagents with agricultural waste. Results: X-ray diffraction confirmed pure anatase phase with crystallite sizes of ~13–20 nm, FESEM revealed quasi-spherical particles averaging ~32.5 nm, and FTIR analysis verified Ti–O lattice vibrations with negligible residual organics. Novelty: The method leverages the phytochemicals in potato peels to simultaneously control nucleation and growth while valorizing bio-waste, offering a low-cost and environmentally benign alternative to conventional routes. Implications: The resultant nanoparticles, exhibiting high crystallinity and uniform morphology, are promising for applications in photocatalysis, dye-sensitized solar cells, and environmental cleanup, highlighting a scalable pathway for sustainable nanomaterial production Highlights: Eco-friendly method using agricultural waste as a natural reducing agent. Pure anatase TiO₂ with nanoscale crystallite size (~13–20 nm). Potential applications in photocatalysis, solar cells, and environmental remediation. Keywords: Green Synthesis, Titanium Dioxide, Potato Peel Extract, Nanoparticles, Photocatalysis